2023
DOI: 10.1177/13524585231188486
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of multiple sclerosis and demyelinating disease in an Asian American population

Jessica H Fan,
Jessa Alexander,
Shane Poole
et al.

Abstract: Background: Race and ancestry influence the course of multiple sclerosis (MS). Objectives: Explore clinical characteristics of MS and neuromyelitis optica spectrum disorder (NMOSD) in Asian American patients. Methods: Chart review was performed for 282 adults with demyelinating disease who self-identified as Asian at a single North American MS center. Demographics and clinical characteristics were compared to non-Asian MS patients and by region of Asian ancestry. Results: Region of ancestry was known for 181 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Specifically, a number of previous studies have suggested that MS has a more aggressive course in people from Black and Hispanic ethnic backgrounds, with earlier onset, more rapid disability progression, greater cognitive and physical impairment, and poorer response to disease-modifying therapies 1021 . Other studies have shown an earlier age at onset in Southeast Asian 22 and South Asian persons 23,24 .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Specifically, a number of previous studies have suggested that MS has a more aggressive course in people from Black and Hispanic ethnic backgrounds, with earlier onset, more rapid disability progression, greater cognitive and physical impairment, and poorer response to disease-modifying therapies 1021 . Other studies have shown an earlier age at onset in Southeast Asian 22 and South Asian persons 23,24 .…”
Section: Introductionmentioning
confidence: 80%
“…Other studies have shown an earlier age at onset in Southeast Asian 22 and South Asian persons 23,24 .…”
Section: Introductionmentioning
confidence: 81%